Epicurean Phantasia - Konstan, David (ΠΗΓΗ/FONS, 2020)
In this paper, I examine the role of phantasia in the Epicurean theory of perception and thought. Making use of newly edited fragments of Epicurus’ Periphuseôs , and recent interpretations of the role of phantasia in Aristotle, along with received texts of Epicurus and Lucretius, I consider such vexed questions as how eidôla or simulacra are reduced in size so as to enter the eye, and the channels by which they are transmitted from the eye to the mind. I discuss further the nature of phantastikê epibolê , that is, “the projection of phantasia ”, and its function in processes of thinking and remembering.
Keywords: eidôla; error; phantasia; phantastikê epibolê; prolepsis; tupos